Minipigs in Translational Immunosafety Sciences: A Perspective. (April 2016) - Rubic-Schneider, Tina; Christen, Brigitte; Brees, Dominique; Kammüller, Michael
The porcine immune system has been studied especially with regard to infectious diseases of the domestic pig, highlighting the economic importance of the pig in agriculture. Recently, in particular, minipigs have received attention as alternative species to dogs or nonhuman primates in drug safety evaluations. The increasing number of new drug targets investigated to modulate immunological pathways has triggered renewed interest to further explore the porcine immune system. Comparative immunological studies of minipigs with other species broaden the translational models investigated in drug safety evaluations. The porcine immune system overall seems functionally similar to other mammalian species, but there are some anatomical, immunophenotypical, and functional differences. Here, we briefly review current knowledge of the innate and adaptive immune system in pigs and minipigs. In conclusion, more systematic and cross-species comparisons are needed to assess the significance of immunological findings in minipigs in the context of translational safety sciences.